A. Pajalich, Il bianco, il nero, il colore. Cinema dell’Impero Britannico e delle sue ex colonie (1929-1972). (Altre Modernità, 2009)
A. Pajalich, Il bianco, il nero, il colore. Cinema dell’Impero Britannico e delle sue ex colonie (1929-1972).